Lecturers’ Acceptance of Gamification in Training and Development: A Conceptual Study - Latip, Siti Nur Nadhirah Abdul; Habib, Md. Mamun; Latip, Muhammad Safuan Abdul (Business and Management Horizons, 2024)
With the rising prominence of e-training across various industries, the integration of gamification principles into organizational training has emerged as a dominant trend. This conceptual study aims to delve into the potential factors influencing the acceptance of gamification among lecturers within the training and development realm. Key variables under scrutiny include attitude, performance expectancy, social influence, perceived enjoyment, and perceived ease of use. The anticipated outcomes of this study are poised to furnish invaluable insights for organizations, particularly within the higher education sector, enabling them to refine their training and development strategies by incorporating gamification methodologies. The ramifications of this study extend beyond individual organizations, offering pertinent recommendations to the broader organizational landscape. By tailoring training programs to cater to the diverse needs and preferences of lecturers, the research contributes to the creation of engaging and effective training initiatives. This investigation aims to address a gap in understanding regarding the dynamics of gamification acceptance within the training and development domain, paving the way for future research endeavors.